PERBAIKAN KUALITAS CITRA DENGAN FUSION UNSUR LOCAL CONTRAST, EXPOSEDNESS DAN SALIENCY - Liska Mirlanda; Lina Lina (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Digital image processing is a branch of engineering informatics. Image processing is an attempt to transform an image or image into another image using certain techniques. The purpose of this application is to improve the quality of the image in the water with the use of test images and imagery training, for image training using images not in the water, and the image of the Laplacian, while the test images using the image of a double Laplacian and white balance with the parameter 0.5, 0.8, 1.0 and 1.2. The design is made in the form of software applications to improve the quality of the image fusion method. For data input will use the White Balance and Laplacian filter as a comparison with the original image taken. Then they will release the data output using the Weight of Fusion that in him there are Local Contrast Weight, Exposedess Weight and Weight saliency. In this resarch, applications using Visual Basic 2012.